Complaint Customer Service Complaint Handling Strategies in Enhancing Customer Satisfaction at Bank Syariah Indonesia KCP Madiun Caruban - Nur Ayu Widia; Fitra Rizal (Journal of Economics and Social Sciences (JESS), 2026)
This study examines how complaint handling strategies implemented by customer service are utilized to enhance customer satisfaction at Bank Syariah Indonesia (BSI) KCP Madiun Caruban. Complaint handling theory emphasizes the importance of being prompt and responsive, providing empathy and a personal approach, offering appropriate and fair solutions, and conducting follow-ups. However, discrepancies between customer expectations and the actual service received persist; therefore, customer service complaint handling strategies need to be analyzed to ensure they are more effective in improving customer satisfaction at BSI KCP Madiun Caruban. This study employs field research with a qualitative approach to gain an in-depth understanding of the customer service complaint handling strategies used to increase customer satisfaction at BSI KCP Madiun Caruban. Data were gathered through semi-structured interviews, direct observations, and Google reviews. The findings indicate that the complaint handling strategies at BSI KCP Madiun Caruban which include being prompt and responsive, showing empathy through a personal approach, providing appropriate and fair solutions, and conducting follow-ups after resolution are generally effective in increasing customer satisfaction. Nevertheless, the promptness and responsiveness aspect still requires improvement. The impact of these strategies is reflected in customer loyalty, service re-use, and positive recommendations. Customer service complaint handling strategies at BSI KCP Madiun Caruban are proven to increase customer satisfaction, although the speed of response still needs to be enhanced.